2004
DOI: 10.1016/j.jacc.2003.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of recurrent atrial fibrillation as documented by an implantable monitoring device

Abstract: This prospective study demonstrates a high incidence of recurrent AF despite optimized antiarrhythmic therapy. Of particular note, AF relapses >48 h remained totally asymptomatic in a significant proportion of patients. Freedom from AF for > or =3 months did not preclude subsequent long-lasting AF recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(81 citation statements)
references
References 29 publications
3
76
0
2
Order By: Relevance
“…1 Studies with transtelephonic arrhythmia monitoring or implantable monitoring devices have reported asymptomatic AF in up to 50% of patients evaluated. 1,2 The patient cohorts observed in most of these studies participated in population surveys such as the Framingham Study, in antiarrhythmic drug trials, or in instances where monitoring followed pacemaker implantation for sinus node dysfunction or atrioventricular block. 1,2 The incidence of asymptomatic arrhythmia in patients presenting with highly symptomatic AF who qualified for radiofrequency (RF) catheter ablation is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies with transtelephonic arrhythmia monitoring or implantable monitoring devices have reported asymptomatic AF in up to 50% of patients evaluated. 1,2 The patient cohorts observed in most of these studies participated in population surveys such as the Framingham Study, in antiarrhythmic drug trials, or in instances where monitoring followed pacemaker implantation for sinus node dysfunction or atrioventricular block. 1,2 The incidence of asymptomatic arrhythmia in patients presenting with highly symptomatic AF who qualified for radiofrequency (RF) catheter ablation is unknown.…”
mentioning
confidence: 99%
“…1,2 The patient cohorts observed in most of these studies participated in population surveys such as the Framingham Study, in antiarrhythmic drug trials, or in instances where monitoring followed pacemaker implantation for sinus node dysfunction or atrioventricular block. 1,2 The incidence of asymptomatic arrhythmia in patients presenting with highly symptomatic AF who qualified for radiofrequency (RF) catheter ablation is unknown. Because AF catheter ablation is a new and potentially curative therapy and is currently performed in an increasing number of patients, data on asymptomatic AF in this subset of patients may have important implications for the overall success rate as well as for the individual patient with regard to concomitant medical therapy, eg, oral anticoagulation.…”
mentioning
confidence: 99%
“…In a study of patients with artificial pacemakers, Israel et al [21] demonstrated a high incidence of AF recurrence >48 h duration in asymptomatic patients. The complications and risks of such silent episodes of AF are believed to be similar to those associated with symptoms [22].…”
Section: Diagnosis Of Afmentioning
confidence: 99%
“…Paroxysmal AF (PAF), also termed intermittent AF, is defined as an episode of AF that terminates spontaneously or with intervention in less than seven days [3]. The frequency of PAF is uncertain, because previous studies have suggested that a majority of these episodes are asymptomatic [4,5], including some that may last more than 48 h [4]. Experienced clinicians can identify AF patterns by visual inspection of the electrocardiogram (ECG) chart.…”
Section: Introductionmentioning
confidence: 99%